HOMOTOPY GROUP OF SPHERES, HOPF FIBRATIONS AND VILLARCEAU CIRCLES - Deep Bhattacharjee,; Sanjeevan Singha Roy,; Riddhima Sadhu, (EPRA International Journal of Research and Development (IJRD), 2022)
Unlike geometry, spheres in topology have been seen as topological invariants, where their structures are defined as topological spaces. Forgetting, the exact notion of geometry, and the impossibility of embedding one into other, the homotopy relates how one sphere of dimensions can wrap another sphere of dimensions